Dynamic Expression and Regulation of Urotensin I and Corticotropin-Releasing Hormone Receptors in Ovary of Olive Flounder Paralichthys olivaceus - Zhou, Hong; Ge, Chunmei; Chen, Aqin; Lu, Weiqun (Frontiers in Physiology, 2019)
Urotensin I (UI), a fish corticotropin-releasing hormone (CRH) like peptide, has been found throughout vertebrate species that has great effects on adaptive physiology comprising stress-related responses and osmotic regulation by binding with CRH type I receptor (CRHR1) and CRH type II receptor (CRHR2) in fish. Dynamic expression and regulation of UI and CRH receptors in the olive flounder ovarian follicle were studied so as to make further efforts to understand the role of UI in the development of teleost ovary. The results showed that stage-specific change in UI mRNA levels in ovarian follicles of olive flounder. UI and CRHR1 mRNA levels were higher in stage III follicles (300~500μm diameter) compared to stage II (90~300μm diameter) and IV (500~800μm diameter) follicles, however, the levels of CRHR2 mRNA were decreased in line with the ovarian development from stage II to stage IV. A strong signal of UI protein was observed in the follicular cells and oocyte in stage III and IV follicles by immunohistochemistry. In vitro treatment of olive flounder ovarian follicles with human chorionic gonadotropin (hCG) showed that the mRNA expression of UI increased significantly at low concentration and decreased at high concentration at 6 h, but the CRHR1 and CRHR2 mRNA did not change obviously. In addition, the results of incubation with 17α, 20β-dihydroxy-4-oregnen-3-one (DHP) show that UI and CRHR1 mRNA expression were elevated with increasing concentrations at 9h. All above results indicated that UI and CRH receptors may have a vital effect on olive flounder ovarian development.